2012
DOI: 10.1111/j.1475-6773.2012.01460.x
|View full text |Cite
|
Sign up to set email alerts
|

What Hospital Inpatient Services Contributed the Most to the 2001–2006 Growth in the Cost per Case?

Abstract: Payers and policy makers may want to explore hospital stay costs that are rapidly rising to better understand their increases and effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 11 publications
(12 reference statements)
0
26
0
Order By: Relevance
“…Nursing practice changes can result in a cost savings if the change reduces nursing labor. The United States spends more money on healthcare than any other country in the world, with an average per capita expense of $8233 compared with an average of $3268 in other industrialized countries 13 . The cost of nursing labor grew 58% in 2002–2009, and this trend is expected to continue 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Nursing practice changes can result in a cost savings if the change reduces nursing labor. The United States spends more money on healthcare than any other country in the world, with an average per capita expense of $8233 compared with an average of $3268 in other industrialized countries 13 . The cost of nursing labor grew 58% in 2002–2009, and this trend is expected to continue 14 .…”
Section: Introductionmentioning
confidence: 99%
“…While the authors did not consider hospital and staffing costs, nor the consequence of possible complications or retreatment rates in a decision analysis, it is important to consider these costs. In the USa, supplies and devices have been implicated as the leading contributor toward rising inpatient costs [39]. While cost of disposables will be highly dependent on world region, industry factors, and logistical conditions, providers should continue to use devices with care and diligence in order to maximize utility.…”
Section: Future Needsmentioning
confidence: 99%
“…Different procedure use, such as percutaneous coronary intervention (PCI) versus coronary artery bypass grafting (CABG), entails different levels of resource intensity, which has been shown to contribute importantly to cross-country differences in cost of AMI hospitalizations (9). Other studies also found that the proportion of patients receiving PCI influences hospitalization costs more than other treatment strategies (10), while changes in the costs of intensive care unit (ICU) contributed substantially to the growth of hospitalization costs in the U.S. (11). Therefore, practices related to PCI, CABG, and ICU use may be important indicators of care patterns and may present opportunities to optimize utilization.…”
Section: Introductionmentioning
confidence: 99%